A reappraisal of success factors for Olympic cross-country skiing - Sandbakk, O.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2014)
Cross-country (XC) skiing has been an Olympic event since the first Winter Games in Chamonix, France, in 1924. Due to more effective training and tremendous improvements in equipment and track preparation, the speed of Olympic XC-ski races has increased more than that of any other Olympic endurance sport. Moreover, pursuit, mass-start, and sprint races have been introduced. Indeed, 10 of the 12 current Olympic competitions in XC skiing involve mass starts, in which tactics play a major role and the outcome is often decided in the final sprint. Accordingly, reappraisal of the success factors for performance in this context is required. The very high aerobic capacity (VO2max) of many of today`s world-class skiers is similar that of their predecessors. At the same time, the new events provide more opportunities to profit from anaerobic capacity, upper-body power, high-speed techniques, and "tactical flexibility." The wide range of speeds and slopes involved in XC skiing requires skiers to continuously alternate between and adapt different subtechniques during a race. This technical complexity places a premium on efficiency. The relative amounts of endurance training performed at different levels of intensity have remained essentially constant during the past 4 decades. However, in preparation for the Sochi Olympics in 2014, XC skiers are performing more endurance training on roller skis on competition-specific terrain, placing greater focus on upper-body power and more systematically performing strength training and skiing at high speeds than previously.